Effects of Ecological Factors on Forest Site Productivity in Crimean Pine Stands of the Kastamonu Region - Seki, Mehmet; Sakıcı, Oytun Emre (Kastamonu University, 2024)
Aim of study: In this study, relationships between ecological factors including topography, climate, soil properties and site productivity of Crimean pine (Pinus nigra J.F. Arnold subsp. pallasiana (Lamb.) Holmboe) stands in the Kastamonu region of Türkiye were investigated. Area of study: The study was conducted in Crimean pine stands of Kastamonu region, northwestern Türkiye. Material and method: A total of thirty-six temporary sample plots inventoried from naturally regenerated pure Crimean pine stands were used in this study. Main results: Our results indicated that climatic factors including precipitation and temperature had the greatest relationship between site productivity. Since climatic factors showed significant differences between the low and high site index classes, they can be reliably used for site classification for this species in the region. Besides, Principal Component Analysis (PCA) showed a strong separation between the poor and high productive sites, considering these variables. The PCA explained 68.7% of the total variation, with PC1 explaining 37.2% and PC2 explaining 31.5% of the data. Research highlights: Crimean pine showed an abstemious characteristic in terms of soil requirements. However, it was also concluded that it has higher growth potential with higher precipitation. The results of this study shows not only an optimal site conditions of Crimean pine, but also additional insights for ecologists and forest managers in determining the decision making for forest management and afforestation applications.